Determining the in-plane orientation of the ground-state orbital of CeCu 2Si 2 - Willers, Thomas; Haverkort, Maurits W. (Physical review letters, 2012)
We have successfully determined the hitherto unknown sign of the B44 Stevens crystal-field parameter of the tetragonal heavy-fermion compound CeCu2Si2 using vector ˆq-dependent nonresonant inelastic x-ray scattering experiments at the cerium N4,5 edge. The observed difference between the two different directions, ˆq∥[100] and ˆq∥[110], is due to the anisotropy of the crystal-field ground state in the (001) plane and is observable only because of the utilization of higher than dipole transitions possible in nonresonant inelastic x-ray scattering. This approach allows us to go beyond the specific limitations of dc magnetic susceptibility, inelastic neutron scattering, and soft x-ray spectroscopy, and provides us with a reliable information about the orbital state of the 4f electrons relevant for the quantitative modeling of the quasiparticles and their interactions in heavy-fermion systems.
Die Ziffer 2 im Titel ist zweimal tiefgestellt
Gesehen am 06.10.2017